Mechanisms of Noise Transmission in Velocity Broad-Band Seismometers: Modeling and Analysis - Yini Sun; Zhongkun Zhang; Zhijuan Zhu; Bin Chen; Lingyun Ye (Applied Sciences)
This paper focuses on the noise transmission process, presenting a comprehensive noise transfer model for velocity broad-band seismometers, which elucidate the transmission mechanisms of five distinct noise sources. We analyzed the spectral characteristics of the noise transfer functions across the forward path, feedback path, and data acquisition stages, with a focus on gains, corner frequencies, and the 0 dB point. Numerical simulations and experiments using the CS60 seismometer showed excellent agreement with theoretical predictions, validating the proposed model and associated noise optimization strategies. This study identified effective methods to reduce noise transfer gains, including optimizing the input and feedback mechanical constants and refining gains at various stages.